Honor to McKinley!' Caricature in Puck Magazine, 1898 - Joseph Ferdinand Keppler::::::::: (Keppler & Schwarzmann, 1898)
Puck' humor magazine (volume XLIII (volume 43), No. 1098) featuring a cartoon caricature of President William McKinley with "Honor to McKinley!" written beneath. On the back side there is a comic titled 'A Lively Find' featuring The African Traveler. Circa March 23rd, 1898.